Students’ Voices on English Language Uses in an Islamic Boarding School in Gorontalo - Fitriyanti Taib; Usman Pakaya; Abid Abid (Univeristas Negeri Gorontalo, 2021)
In the Islamic boarding school settings as in Indonesia, all the students are required to master English language for their daily interaction, starting from year 7 up to 12. However, the students who are beginners may often feel challenged with it. The present of study, therefore, seeks to discover the students’ voices on English language uses outside classroom context at one of the Islamic boarding schools located in the Province of Gorontalo. The participants of this study were the students sitting at the junior high school level. Informed by a qualitative approach, data were collected by using observation fieldnotes and interview protocols, and analyzed using a thematic analysis. The findings showed that there were four themes representing students’ voices: lack of preparation, language learning preference, language use preference, and English use challenges. The findings suggest that the boarding school may need to create programs that encourage the students to learn and master English, and to facilitate them in making the most of their English language learning.